2017
DOI: 10.1159/000454854
|View full text |Cite
|
Sign up to set email alerts
|

Treatable Leukoencephalopathy in a Patient with Hypophosphatemia

Abstract: We report the first patient with pathologically proven leukoencephalopathy associated with hypophosphatemia. A 61-year-old woman had repetitive episodes of decreased consciousness with pontine and pallidal lesions and extensive leukoencephalopathy on MRI, later found to be associated with hypophosphatemia. Although hypophosphatemia has been linked to central pontine and extrapontine myelinolysis (osmotic myelinolysis), lesions in the deep white matter have not been reported. Brain biopsy performed during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…A study on hypophosphatemia after nontraumatic intracranial hemorrhage showed that acute hydrocephalus and diffuse brain edema were more common in patients with hypophosphatemia; however, there was no difference in outcome between hypophosphatemic and normophosphatemic patients [109]. Hypophosphatemia can also cause leukoencephalopathy, which can be corrected with treatment [110]. Other neurological illnesses, such as osmotic demyelination syndrome, have been described to be also associated with hypophosphatemia [111].…”
Section: The Impact Of Hypophosphatemia On Neurological Disordersmentioning
confidence: 99%
“…A study on hypophosphatemia after nontraumatic intracranial hemorrhage showed that acute hydrocephalus and diffuse brain edema were more common in patients with hypophosphatemia; however, there was no difference in outcome between hypophosphatemic and normophosphatemic patients [109]. Hypophosphatemia can also cause leukoencephalopathy, which can be corrected with treatment [110]. Other neurological illnesses, such as osmotic demyelination syndrome, have been described to be also associated with hypophosphatemia [111].…”
Section: The Impact Of Hypophosphatemia On Neurological Disordersmentioning
confidence: 99%
“…Sunorminus fosfatų kiekį kraujo serume, sąmonės pritemimo epizodai nesikartojo, MRT pokyčiai išnyko. Hipofosfatemija gali sąlygoti leukoencefalopatiją, kurią galima koreguoti [28]. Klinikinis atvejis: 58 metų vyras, sergantis užleista stemplės karcinoma, sukėlusia užpakalinės grįžtamos encefalopatijos sindromą (UGES).…”
Section: Rezultataiunclassified